Time to reconsider Spitzoid neoplasms? - Carmelo Urso (Mattioli1885, 2016)
Background: Spitzoid neoplasms may pose significant diagnostic problems because in a fraction of them it is quite difficult or impossible to establish if they are benign or malignant lesions. An extraordinarily large number of studies have been made in attempts to solve this problem; regrettably, the histological criteria proposed and the various special sophisticated techniques employed have proven to be ineffective in making this distinction with confidence. Objectives: To explore the possible causes for this diagnostic failure and an attempt to identify the source of this problem. Method: A historical and technical analysis of the specialized literature is performed, critically evaluating the main points of this controversial topic. Results: The reasons for the diagnostic failure in Spitzoid neoplasms are not clear but could be the result of inappropriate conceptual classification. The analysis of available data and a rational review of old and new assumptions and concepts may suggest a different classification for Spitzoid neoplasms: Spitz nevus, atypical Spitz tumor and Spitzoid melanoma, rather than being three different tumors that are difficult or impossible to distinguish with assurance, could be viewed as one unique entity, Spitz tumor (ST). A Spitz tumor is a low-grade malignant neoplasm, in which the amount of intrinsic risk is variable, ranging from very low to high (ST1, ST2, ST3), and malignant potential could be estimated. Conclusions: The proposed alternative classification of Spitzoid neoplasms as a unique tumor may help in overcoming the difficulty in diagnosis of these tumors.